Revolutionizing Rigid Pavements Towards Magnetizable Concrete Materials for Charging Electric Vehicles - Mohamed Abdel Raouf; Yassien Zidan; Hana Alnaas; Rand Abo ElEnain; Abdullah Mahmoud; Mahmoud Seddik; Mayar Mohamed Khairy; Mohamed Nagib Abou-Zeid (Journal of Building Materials and Structures)
Nowadays, the green economy dictates the urge for finding innovative construction materials to be compatible with the future needs. The growing potential of electric vehicles (EVs) necessitates the transformation towards sustainable and magnetizable concrete pavement. The primary objectives of this work are to determine the optimal materials and mixing proportions to produce high-performance magnetizable mortars for pavement applications. The experimental testing program includes assessing the magnetic properties through the inductance test, the fresh properties using the mini-slump test, the hardened properties through the compressive strength at 3, 7, and 28 days, and the durability through chemical soundness and abrasion resistance. It may be concluded that the magnetic properties of Portland cement mortars can be enhanced through the incorporation of natural magnetite (25% replacement), slag (25% replacement), and scrap iron fillings (70% replacement), and importantly, the addition of enhancers such as magnets, steel mesh, and/or steel bars. These magnetizable mortars can be used for rigid pavement applications since they have a higher abrasion resistance.